2003
DOI: 10.1021/jf026027e
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Model for the Glucose−Fructose−Glycine Browning Reaction

Abstract: The browning of glucose-fructose-glycine mixtures involves parallel glucose-glycine and fructose-glycine reactions, which share a common intermediate, the immediate precursor of melanoidins in the kinetic model. At pH 5.5, 55 degrees C glucose is converted into this intermediate in a two step process where k(1) = (7.8 +/- 1.1) x 10(-)(4) mol L(-)(1) h(-)(1) and k(2) = (1.84 +/- 0.31) x 10(-)(3) h(-)(1) according to established kinetics, whereas fructose is converted into this intermediate in a single step wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…The e 420 of nondialyzable (>3.5 kDa) glucose-glycine melanoidins (both at 120°C, pH 6.8 and at 100°C, pH 5.5) was found to be 1.01 ± 0.02 l mmol À1 cm À1 and those of HMW (>12.4 kDa) melanoidins from glucose/fructose-glycine/asparagine/lysine basic reactions (at 145°C for 2 h) fell between 0.50-0.76 l mmol À1 cm À1 (Kim & Lee, 2009;Martins & van Boekel, 2003). Moreover, Mundt and Wedzicha (2003) determined a e 470 of 0.48 ± 0.02 l mmol À1 cm À1 using the kinetic model for melanoidins produced from the fructose-glycine reaction, which is half the value determined for melanoidins from the glucose-glycine reaction (0.96 ± 0.04 l mmol À1 cm À1 ). Bekedam et al (2006) demonstrated that use of the specific extinction coefficient (K) was preferable to the molar extinction coefficient (e), since the molecular weight of melanoidins is unknown and probably variable.…”
Section: Quantification Of Model Melanoidinsmentioning
confidence: 91%
“…The e 420 of nondialyzable (>3.5 kDa) glucose-glycine melanoidins (both at 120°C, pH 6.8 and at 100°C, pH 5.5) was found to be 1.01 ± 0.02 l mmol À1 cm À1 and those of HMW (>12.4 kDa) melanoidins from glucose/fructose-glycine/asparagine/lysine basic reactions (at 145°C for 2 h) fell between 0.50-0.76 l mmol À1 cm À1 (Kim & Lee, 2009;Martins & van Boekel, 2003). Moreover, Mundt and Wedzicha (2003) determined a e 470 of 0.48 ± 0.02 l mmol À1 cm À1 using the kinetic model for melanoidins produced from the fructose-glycine reaction, which is half the value determined for melanoidins from the glucose-glycine reaction (0.96 ± 0.04 l mmol À1 cm À1 ). Bekedam et al (2006) demonstrated that use of the specific extinction coefficient (K) was preferable to the molar extinction coefficient (e), since the molecular weight of melanoidins is unknown and probably variable.…”
Section: Quantification Of Model Melanoidinsmentioning
confidence: 91%
“…There are 'diverging' results concerning the relative reactivities of fructose and glucose (Laroque et al, 2008) depending on the conditions employed. It has been shown that the relative reactivities of glucose and fructose vary with respect to the conditions of the reaction and the composition of the reaction mixture (Laroque et al, 2008;Mundt and Wedzicha, 2003). Browning intensity was higher for fructose-glycine systems compared to glucoseglycine systems when the glycine concentration was low, but when the amount of glycine was increased, the results were inverted (Kato et al, 1969).…”
Section: Influencing the Early Stage: The Role Of Amino Acidmentioning
confidence: 99%
“…They both proposed that, at low pH, the reaction could proceed directly from the 1,2‐enol, bypassing the keto form of the ARP. In another study, when a ketose (fructose) was incorporated into the glucose–glycine system, the kinetics demonstrated that the formation of colour from fructose was a two‐step reaction, passing through just one intermediate which corresponded to Int2 in Fig. .…”
Section: Mechanistic Modelling Of the Maillard Reactionmentioning
confidence: 97%